APPLYING THE GLOBAL PRINCIPLES OF THE SUSTAINABLE DEVELOPMENT FOR BETTER QUALITY OF LIFE - Šimonová, Stanislava; Foltánová, Nikola (Žilinská univerzita, 2018)
Improving the quality of life is a global strategic goal. It is the long-lasting goal which is supported by the projects at the national, European and even the world level. International project ‘Healthy Cities’ represents active movement of the European municipalities which systematically proceed with the health of their citizens. A conception of the ‘Corporate Social Responsibility’ motivates organizations and municipalities to contribute the sustainable development and urge better quality of life of their employees, local commonwealth and the society. Concrete realization of the recommended principles is done by help of various tools. There are for example ‘Agenda 21’with emphasis on planning the further development of the region in harmony with principles of the sustainable development and with emphasis on public involvement. Another method is ‘CAF’ for performing continuous self-assessment. Application of these principles at the level of municipalities’ administration should contribute to the regional development and to the improvement of the quality of life of their citizens. Its own realization is done at the bigger municipalities where the agenda could be done by specific workers exactly trained for it. Small municipalities do not have these possibilities – they have low knowledge about the above mentioned procedures or are afraid of the situation that agenda might be complex or unusable for them. This text is aimed at these small municipalities and to the assessment of the procedures and usable activities which might contribute to good mastering in the meaning of global strategic goal, which is better quality of life.
Uplatňování principů udržitelného rozvoje pro zvyšování kvality života
Keywords: quality of life; sustainable development; Local Agenda 21; CAF